Dual-Task (Cognitive Plus Sucking) Training for Stroke Patients: A Randomized Controlled Study. - Tang, Qiaomin; Sun, Yuanyuan; Hu, Chen; Wang, Qiaoni; Jin, Jingfen (Perceptual & Motor Skills, 2025)
Our aim in this study was to determine the effect of applying dual-task training of cognitive rehabilitation and sucking activities for stroke patients. We selected 118 stroke patients from the Neurology Department of a class 3, grade A hospital between August 2020 and January 2022; and we randomly assigned them into either a dual-task (DT) training group or a control group. The DT training group received dual-task training of cognition combined with sucking activities based on conventional nursing guidelines; the control group received only conventional neurologic nursing procedures. After a 4-week intervention period, swallowing ability, sucking force, Swallowing Quality-of-Life Questionnaire (SWAL-QOL) scores, and Mini-Mental State Examination (MMSE) scores improved significantly for patients in both groups (p =.010, p <.001, p <.001, p <.001). And the incidence of clinical aspiration pneumonia was much lower in the DT training group than in the control group (p =.024). We concluded that short-term dual-task training of cognition combined with sucking activities effectively improved the sucking force, swallowing abilities, SWAL-QOL, and cognition functions of these stroke patients, with important implications for other stroke patients.